TRANSIENT REMISSION OF ACROMEGALY FOLLOWING PITUITARY APOPLEXY AND EARLY RELAPSE: A CASE REPORT - Teh, Kai Xuan; Ho, Jin Hui; Tee, Hwee Ching (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Acromegaly is caused by excessive growth hormone (GH) secretion and secondary elevation of insulin-like growth factor-1 (IGF-1). Elevated serum IGF-1 level is a useful screening tool for acromegaly. However, IGF-1 levels may appear normal in conditions such as liver disease, malnutrition, uncontrolled diabetes mellitus and pituitary apoplexy. When serum IGF-1 levels are normal, it is easy to miss the diagnosis of acromegaly without a high index of suspicion and/or a GH suppression test. We report a case of an acromegaly patient with pituitary apoplexy and initially normal IGF-1 level. CASE A 24-year-old young female presented initially with severe headache, blurring of vision, vomiting and sudden onset of reduced consciousness. Brain CT showed intratumoral haemorrhage of sellar and suprasellar mass causing cerebral oedema and mass effect, suggestive of pituitary apoplexy. Emergency craniectomy and tumour excision were performed, and HPE revealed a pituitary adenoma. Hormonal workup prior to surgery showed central hypothyroidism with hyperprolactinemia, likely caused by stalk effect. Other parameters were unremarkable, including normal IGF-1. Postoperatively, she developed panhypopituitarism, bilateral eye blindness and scar epilepsy. IGF-1 was rechecked 6 months postoperatively for spade-like hands, but the result was not found. It was only after four years, following family concerns about gradual acral enlargement, that her post-op IGF-1 was found markedly elevated. GH suppression test subsequently confirmed acromegaly. She was offered repeat surgery due to the persistent sellar mass from MRI surveillance. However, the patient was not keen and medical therapy with a somatostatin receptor ligand was initiated, with referral to oncology for radiotherapy. CONCLUSION Transient remission of acromegaly after pituitary apoplexy can occur. However, a high index of suspicion of relapse is crucial especially in those patients with acromegaloid features. Hence, repeating IGF-1 testing or GH suppression test is advisable if the diagnosis is uncertain.